If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a + 3a + 5b + 11b = 0 Combine like terms: 7a + 3a = 10a 10a + 5b + 11b = 0 Combine like terms: 5b + 11b = 16b 10a + 16b = 0 Solving 10a + 16b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-16b' to each side of the equation. 10a + 16b + -16b = 0 + -16b Combine like terms: 16b + -16b = 0 10a + 0 = 0 + -16b 10a = 0 + -16b Remove the zero: 10a = -16b Divide each side by '10'. a = -1.6b Simplifying a = -1.6b
| 2x^2+10x+13=0 | | (4i)/(4-i) | | -82=m+2(-6m-8) | | 6(2X+1)=252 | | X=10cosx | | g(x)=x+14 | | 2345678347756846876427867478968763276878684348237682764878736+73642675682385678482486747= | | g(y+6)= | | (3x-1)/4-2x+1/5=(7x-13)/20 | | 32+5=2x+13 | | 0=1.5x^2-8x+8 | | 2x+4x+3y-y= | | -3m+1=9-15 | | 104=2(x+16)+x | | r=1/3d(60-t) | | -5x-4=16+x | | 2x+40=4x+22 | | D(t)=4.9t^2-0.1t^3 | | 8x+204=6x+180 | | |2-5|= | | 3(2n+4)=30 | | 6x-16=104 | | 7-9z=81+z | | 4x^2-19x+17=-6x+7 | | 4r+(7*4)=72 | | 3a-5=18 | | F(x)=4x-3x^2-x^3 | | D(t)=4.9t^2 | | 2-(3x-20)=11-10x | | =x(24-2x)(45-2x) | | x^2+y^2-7x-7y+12=0 | | 3x-2/8=40 |